Sistem Informasi Akademik Berbasis Website Pada SMK YPIA Cimanggu - Ratih; Evi Desriyani (Jurnal Teknologi dan Bisnis, 2021)
Currently, academic data processing activities at YPIA Cimanggu Vocational School are still done manually, academic data storage is still stored in Microsoft Word and Microsoft Excel files stored on certain devices or flash drives, this sometimes makes it difficult for teachers and staff of YPIA Cimanggu Vocational School to access academic data because Accessing data can only be done with certain devices or flash drives that take a relatively long time. To overcome these obstacles, it is necessary to have an integrated web-based academic information system, to simplify and speed up inputting, processing, and accessing data anywhere at any time so that time is used more efficiently. In making this website-based academic information system, using the waterfall method and several tools such as PHP, MySQL, HTML and CSS. The results obtained are in the form of a web-based academic information system that presents data in an integrated manner, to facilitate the process of inputting, processing data, and facilitating access to academic data anywhere at any time so as to increase efficiency and time effectiveness, in addition so that the academic information system created can be used optimally. it is necessary to have training so that users can better understand the system and how to use it and the current system can be developed to be more complex. Keywords: Academic Information System, Website, Waterfall Method, PHP, MySQL, HTML, CSS